"Erinnerungen an die Zukunft." Foto von Massenveranstaltung in Berlin. Herausgegeben zur Bundestagswahl am 2.12.1990 - Fischer, Irene, (1990)
"Erinnerungen an die Zukunft." Foto von Massenveranstaltung in Berlin. Herausgegeben zur Bundestagswahl am 2.12.1990.